Protective Effect of Prim-O-Glucosylcimifugin on Ulcerative Colitis and Its Mechanism - Yu Yin; Kunjian Liu; Guofeng Li (Frontiers Media S.A., 2022)
Intestinal epithelial immune dysfunction or imbalance in the homeostasis of intestinal flora can lead to the occurrence or exacerbation of ulcerative colitis (UC). Prim-O-glucosylcimifugin (POG) is an extract of Chinese traditional medicine (TCM) Saposhnikov, which has analgesic, anti-inflammatory, and antioxidant effects. The present work discussed how the POG alternated ulcerative colitis (UC) along with its underlying mechanism. This was clarified by performing animal studies in a mice model, wherein UC was induced by dextran sulfate sodium (DSS). In vivo studies have found that POG increased clinical score, colonic length, and weight of mice in the ulcerative colitis model. It repaired the pathological injury of an intestinal mucosa within mice while inhibiting the inflammatory factor levels such as IL-1β, TNF-α, and IL-6. Meanwhile, by16SrDNA sequencing analysis, it was found that POG regulated the richness of intestinal microbiota structure and repaired the intestinal immune barrier by upregulating the expression levels of tight junction proteins Occludin, Claudin-3, and ZO-1. To further confirm the above results, we found in in vitro studies that POG also protected lipopolysaccharide- (LPS-) induced RAW264.7 cells. POG dramatically suppressed inflammatory factor production (including TNF-α, IL-1β, and IL-6) within LPS-treated RAW264.7 cells by inhibiting the activation of ERK1/2, AKT, JNK1/2, IκB-α, P38, and P65 phosphorylation. In conclusion, POG plays a protective role against UC by inhibiting the activation of pro-inflammatory signaling pathways MAPK, AKT, and NF-κB; repairing the integrity of the intestinal barrier; and regulating the diversity and abundance of intestinal flora.